2018
DOI: 10.1038/s41598-018-31637-6
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Morphological Features of Aortic Aneurysms Drive Intraluminal Thrombus

Abstract: Over 75% of abdominal aortic aneurysms harbor an intraluminal thrombus, and increasing evidence suggests that biologically active thrombus contributes to the natural history of these potentially lethal lesions. Thrombus formation depends on the local hemodynamics, which in turn depends on morphological features of the aneurysm and near vasculature. We previously presented a hemodynamically motivated “thrombus formation potential” that predicts where and when thrombus might form. Herein, we combine detailed stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Bhagavan et al 47 computationally examined the roles of five key morphologic features of AAAs on ILT formation: AAA diameter, AAA length, axial position, tortuosity, and renal artery position. They concluded that the maximum diameter is a key determinant, with vortex flow structures having the potential to induce thrombogenicity and, therefore, ILT deposition.…”
Section: Mechanical Properties and Hemodynamics Of Iltmentioning
confidence: 99%
“…Bhagavan et al 47 computationally examined the roles of five key morphologic features of AAAs on ILT formation: AAA diameter, AAA length, axial position, tortuosity, and renal artery position. They concluded that the maximum diameter is a key determinant, with vortex flow structures having the potential to induce thrombogenicity and, therefore, ILT deposition.…”
Section: Mechanical Properties and Hemodynamics Of Iltmentioning
confidence: 99%
“…Generally, there are two approaches to investigate the correlation between morphology and flow: (a) use patient‐specific models and correlate morphological features with flow response, or (b) use idealized models where morphological features are parameterized, often combined with one or two patient‐specific geometries to confirm the results . On the one hand, patient‐specific models are realistic but would require an extensive database of segmented surfaces to isolate the effect of a single morphological feature in a multifactorial disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of abdominal aortic aneurysms, although a different disease, aneurysm morphology and hemodynamics have been linked to intraluminal thrombus formation which has been identified as one of the drivers of aortic aneurysm progression. 20,21 Furthermore, hemodynamic and morphological factors, in combination with clinical data and shape of the intra-luminal thrombus, have been proposed as predictors of aortic aneurysm growth using data from longitudinally followed abdominal aortic aneurysms. 22 In contrast, intra-aneurysmal thrombus is rare in cerebral aneurysms and it mostly observed in large or giant aneurysms (>25 mm), and the mechanisms for their evolution remains unclear.…”
Section: Introductionmentioning
confidence: 99%